2021
DOI: 10.1155/2021/5572395
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative Biliary Drainage with or without Pancreatic Stenting on Complications after Pancreatoduodenectomy: A Retrospective Cohort Study

Abstract: Background. The necessity of preoperative biliary drainage (PBD) prior to pancreaticoduodenectomy (PD) is still controversial. However, in some settings, PBD with endoscopic retrograde cholangiopancreatography (ERCP) procedure is recommended as a preferred management. Meanwhile, pancreatic duct stenting in the drainage procedure is rarely performed for selected indications, and its associated complications after PD remain quite unknown. Methods. A retrospective observational longitudinal cohort study was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
0
1
1
Order By: Relevance
“…Regarding postoperative hemorrhage, intraabdominal abscess, POPF, and DGE, our results were similar to a retrospective study conducted at Massachusetts General Hospital, showing no considerable difference between patients who received ERBD and no PBD patients [ 23 ]. Although some studies have reported an increase in postoperative DGE [ 24 , 26 ], we did not observe any significant difference between ERBD and no PBD groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding postoperative hemorrhage, intraabdominal abscess, POPF, and DGE, our results were similar to a retrospective study conducted at Massachusetts General Hospital, showing no considerable difference between patients who received ERBD and no PBD patients [ 23 ]. Although some studies have reported an increase in postoperative DGE [ 24 , 26 ], we did not observe any significant difference between ERBD and no PBD groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Od kilku lat dostępna jest nowa technika drenażu dróg żółciowychdrenaż w asyście endosonografii (endoscopic ultrasound-guided biliary drainage -EUS-BD), który może być korzystną alternatywą dla drenażu przezskórnego [9]. Badania kliniczne wykazały jednak, że mimo normalizacji wyników badań laboratoryjnych u pacjentów z guzami głowy trzustki odsetek powikłań pooperacyjnych po pankreatoduodenektomii poprzedzonej zabiegiem drenażowym nie jest mniejszy niż u pacjentów operowanych z żółtaczką mechaniczną bez drenażu [10,11,12,13,14]. Zakładając, iż przedoperacyjny drenaż dróg żółciowych nie poprawia wyników operacji, pojawia się pytanie, kiedy chorego należy operowaćtak szybko, jak to możliwe, czy po upływie pewnego czasu.…”
Section: Introductionunclassified